Notes of an Overland Journey Through France and Egypt to Bombay - Roberts, Emma, 1794?-1840 (Salt Lake City, UT : Project Gutenberg, 2004)
"Notes of an Overland Journey Through France and Egypt to Bombay" by Emma Roberts is a travel narrative written in the early 19th century. This account depicts the author's adventurous journey as she travels from London to Bombay, offering vivid descriptions of her experiences in France, Egypt, and eventually India. The narrative highlights the places she visits, the people she encounters, and her reflections on the cultural contrasts between Europe and the East. The opening of the book introduces the reader to Roberts' journey beginning with her departure from London aboard a French steamer. She provides detailed observations of the weather, the ship's ambiance, and the discomforts of travel, such as challenging sea conditions and delays. As she arrives at Havre, Roberts experiences the initial difficulties of customs, but also takes time to appreciate her surroundings. Through her descriptive prose, she lays the groundwork for an engaging travelogue that promises insights into the landscapes, societies, and customs she will explore throughout her journey to Bombay. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by Paul Murray, Leah Moser and the Online Distributed Proofreading Team
Keywords: Voyages and travels; France -- Description and travel; Egypt -- Description and travel; Bombay (India) -- Description and travel